Innovation Management: A Bibliometric Analysis of Research Hotspots and Citation Dynamics - Loso Judijanto; Yendri Deswin (West Science Business and Management, 2026)
This study aims to map the intellectual structure, research hotspots, and citation dynamics in innovation management literature through a bibliometric approach. Data were collected from the Scopus database within a defined publication period and analyzed using VOSviewer to examine keyword co-occurrence, co-citation patterns, and thematic evolution. The results reveal that innovation management research is structured around three major thematic domains: sustainability-driven innovation, technology-enabled innovation, and human-centered applications. Key research hotspots include sustainable development, artificial intelligence, knowledge management, and healthcare innovation. The analysis also indicates a significant shift from traditional firm-centric innovation toward interdisciplinary and impact-oriented approaches that integrate environmental, technological, and social dimensions. Citation dynamics highlight the growing influence of digital transformation and sustainability paradigms in shaping contemporary research. This study contributes by providing a comprehensive overview of the evolution and current landscape of innovation management, offering insights into emerging trends and future research directions.